Research of problems and prospects of economic adaptation of military servicemen: sociological and statistical analysis - Nazarova, Galyna; Sotnikova, Yuliia; Luhova, Viktoriia; Klyzub, Oleksii; Ivashchenko, Mykola (Technology audit and production reserves, 2025)
The object of research is the system of economic adaptation of military personnel returning to civilian life after participating in hostilities during the full-scale war in Ukraine. As a result of the conducted analysis and sociological research, several key deficiencies in the functioning of this system were identified, including: insufficient level of state support during the transition to civilian employment, low level of informational assistance, difficulties with job placement, and limited access to retraining and entrepreneurial development. To identify and address these shortcomings, a comprehensive approach was applied, including statistical analysis of the labor market, regional analysis of job vacancies, study of veteran support initiatives, and a sociological survey of servicemen using an online questionnaire. These methods made it possible not only to detect weaknesses in the adaptation system but also to develop proposals for its improvement. The study found that 58 % of military personnel are only partially prepared for reintegration into civilian life. The main reserves for improving adaptation include expanding access to training programs (noted by 48 % of respondents), promoting entrepreneurship (important to 34 %), and developing digital and creative skills (needed by 22 % and 28 %, respectively). The results also revealed a high potential for self-employment among veterans, with 26 % intending to start their own business, which could become a growth driver for regional economic activity. The authors interpret the results by asserting that effective economic adaptation is achievable through the creation of an integrated institutional support model. This model should combine state policy, digital labor market tools, human capital development, and the utilization of veterans’ creative potential. The results of the sociological study of the needs of military personnel, presented in the article, give grounds to argue about the possibility of their involvement in entrepreneurial activity. Such an integrated system can ensure not only employment but also economic self-realization and sustainable reintegration of veterans into post-war society.